PELATIHAN PEMBUATAN PERATURAN DESA DI KECAMATAN BANJARAN, MAJALENGKA - Akhmaddhian, Suwari (Empowerment, 2020)
Improving the quality of human resources is very important especially the quality of the village government apparatus which is the frontline in confusion with the community. The purpose of this counseling is that the village apparatus understand related to making regulations in the village scope so that village regulations have good standards namely philosophical aspects, sociological aspects and juridical aspects. The method used is by way of lectures and discussions then ends with questions and answers. The results obtained from this community service are village officials who understand the technical procedures and theoretical procedures for making regulations in the village scope ranging from village regulations, village head regulations and other regulations. The knowledge and skills of the village apparatus in making regulations are very necessary so that in making a regulation it is always beneficial for the village community.Keywords: Village regulations, philosophical aspects, sociological aspects and juridical aspects. AbstrakPeningkatan kualitas sumberdaya manusia sangat penting khususnya kualitas aparatur pemerintah desa yang merupakan garda terdepan dalam bersingungan dengan masyarakat. Tujuan dari diadakannnya penyuluhan ini yaitu para aparatur desa memahami terkait dengan pembuatan peraturan di lingkup desa sehingga peraturan desa memiliki standar yang baik yaitu aspek filosofis, aspek sosiologis dan aspek yuridis. Metode yang digunakan yaitu dengan cara ceramah dan diskusi kemudian diakhiri dengan tanya jawab. Hasil yang diperoleh dari pengabdian kepada masyarakat ini yaitu aparatur desa memahami tatacara secara teknis maupun sacara teoritis pembuatan peraturan di lingkup desa mulai dari peraturan desa, peraturan kepala desa serta peraturan lainnya. Pengetahuan dan keterampilan aparatur desa dalam membuat peraturan sangat diperlukan sehingga dalam membuat  suatu peraturan senantiasa bermanfaat bagi masyarakat desa.Kata Kunci: Peraturan desa, aspek filosofis, aspek sosologis dan aspek yuridis.